PENGARUH STRES KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PRIMAYA HOSPITAL KOTA TANGERANG - Nurochman, Nurochman; Sudiarto Sudiarto (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
at Primaya Hospital, Tangerang City, both partially and simultaneously. This study uses a quantitative method with a descriptive approach. The technique for determining the sample size used in this study uses the Slovin method. Based on the existing population of 420 people, the number of samples used in this study if calculated using the Slovin method is 80.76 which is rounded up to 81 respondents. Data collection uses a questionnaire with a Likert scale. Data analysis is carried out through validity tests, reliability tests, classical assumption tests, simple and multiple linear regression analysis, and hypothesis testing through t-tests and F-tests. The results of the study indicate that partially, job stress has a positive and significant effect on employee performance with a regression equation of Y = 6.729 + 0.836 X1 and a calculated t-value > t-table (10.398 > 1.990) with a significance of 0.00 < 0.05. Therefore, H0 is rejected and H1 is accepted. Compensation also has a positive and significant effect with the regression equation Y = 6.431 + 0.877 X2 and the calculated t-value > t-table (12.353 > 1.990) with a significance of 0.00 < 0.05. So, H0 is rejected and H2 is accepted. Simultaneously, work stress and compensation have a significant effect on employee performance with the regression equation Y = 2.709 + 0.414 X1 + 0.593 X2 and the calculated F value > F table (105.991 > 3.11) with a significance of 0.00 < 0.05. So, H0 is rejected and H3 is accepted.